2019
DOI: 10.1021/acs.jmedchem.8b01041
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent, Selective, and Orally Bioavailable Inhibitors against Phosphodiesterase-9, a Novel Target for the Treatment of Vascular Dementia

Abstract: To identify phosphodiesterase-9 (PDE9) as a novel target for the treatment of vascular dementia (VaD), a series of pyrazolopyrimidinone analogues were discovered based on a hit 1. Hit-to-lead optimization resulted in a potent inhibitor 2 with excellent selectivity and physicochemical properties to enable in vivo studies. Oral administration of 2 (5.0 mg/kg) caused notable therapeutic effects in the VaD mouse model, providing a promising lead or chemical probe for investigating the biological functions of PDE9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…In our studies aiming to discover novel PDE9 inhibitors and their novel potential therapeutic applications, a hit compound LL01 with an IC 50 value of 49 nM and a moderate T 1/2 of 8.03 min in rat liver microsomes (RLMs) was developed. 16 To obtain lead compounds with better microsomal stability, further structural optimization of compound LL01 was performed via structurebased design approaches such as molecular docking and dynamics simulations, which allowed us to save our synthetic efforts. A redocking of the inhibitor 28 s in the crystal structure (PDB ID: 4GH6) was performed to validate the docking approach suitable for PDE9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our studies aiming to discover novel PDE9 inhibitors and their novel potential therapeutic applications, a hit compound LL01 with an IC 50 value of 49 nM and a moderate T 1/2 of 8.03 min in rat liver microsomes (RLMs) was developed. 16 To obtain lead compounds with better microsomal stability, further structural optimization of compound LL01 was performed via structurebased design approaches such as molecular docking and dynamics simulations, which allowed us to save our synthetic efforts. A redocking of the inhibitor 28 s in the crystal structure (PDB ID: 4GH6) was performed to validate the docking approach suitable for PDE9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…described in our previous report. 16 3 H-cGMP was the substrate for the biological test using PDE9A2. 3 H-cGMP was diluted with the assay buffer, which contained 20−50 mM Tris−HCl (pH 8.0), 10 mM MgCl 2 , and 1 mM dithiothreitol to 20,000−30,000 cpm per assay.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies suggested that introducing certain heterocyclic rings (especially those containing fluorine atoms), other than piperidine rings, were useful for the improved metabolic stability of PDE inhibitors [ 17 , 18 ]. For DIP, its piperidine rings made fewer key interactions than diethanolamine chains with PDE5.…”
Section: Introductionmentioning
confidence: 99%
“…Some stud-ies have even shown that VD coexists in clinical patients with Alzheimer's disease; the combination often increases the difficulty of treatment [5]. VD is the only type of dementia that can be prevented by early treatment [6]. Risk factors for VD development include hyperlipidemia, hypertension, diabetes mellitus, and tobacco use.…”
Section: Introductionmentioning
confidence: 99%